Profitability and technical efficiency of auto rice mills in Bangladesh - Rahman, Md Mahbubur (2013)
This study is concerned with the profitability and technical efficiency of the selected Auto Rice Mills (ARMs) in Bangladesh. It has made use of data collected from 35 ARMs from the districts of Naogaon, Dinajpur, Mymensingh, Sherpur and Kustia. A structured questionnaire was used to collect the information. The specific objectives of the study are: i. to estimate cost, return and profitability of the ARMs, ii. to determine overall technical efficiency, pure technical efficiency and scale efficiency of the ARMs and iii. to identify factors affecting operation of ARMs. Farm management method has been applied to determine gross margin, net margin, break-even price and break-even production, while Data Envelopment Analysis (DEA) method is used to determine the technical and scale efficiency of the ARMs. An average rice mill was required to spend US$ 5.31 million per year for its paddy processing operations. The variable cost constituted 98.65% while the fixed cost formed only 1.35% of the total cost. Two most important components of the total costs are for paddy and energy, which constitutes about 92.00% and 4.00% respectively. The total revenue of the rice mills comprises 86.14% of polished rice, 4.31% of bran, 4.78% of broken rice, 1.60% of black/dead rice and 2.90% worth of husk. Gross margin and net margin per year ARM are US$ 1.00 million and US$ 0.93 million respectively. As net margins are positive, the ARMs appear to be sustainable not only in the short-run but also in the long-run. The gross and net margins per metric tonne of polished rice are US$ 79.65 and US$ 73.99 respectively. The break-even price per metric tonne of polished rice was found to be US$ 418 while the average break-even production of polished rice was 12,436 metric tonne suggesting also that the mills were running at profit. The overall technical efficiency score of the rice mills is found to be 0.898 comprising 95.80% of pure technical efficiency and 93.70% of scale efficiency. Pure Technical Efficiency score suggeests that ARMs operate at about 4% below their frontier production, which means thatt 4% more polished rice could be produced with the existing levels of inputs use if all mills are operating at full efficiency level. About 46% ARMs achieved 100% pure technical efficiency score. The mean scale efficiency was 0.937. Percent of ARMs operated at decreasing returns to scales, constant returns to scales and increasing returns to scales are 6, 71 and 23% respectively. The overall average excess inputs usage levels are 24.26% for investment, 10.02% for paddy, 10.23% for labour, 12.06% for energy and 21.65% for default capacity. Problems faced by the auto rice millers are disrupted electricity supply, anti-holding act, existence of too many rice mills, high transport cost, seasonality of paddy supply, non-availability of skilled person to deal with breakdown, failure and maintenance , and finally scarcity of running capital.